Clinical management and humoral immune responses to rabies post‐exposure prophylaxis among three patients who received solid organs from a donor with rabies. Issue 3 (19th May 2015) - Vora, N.M.; Orciari, L.A.; Niezgoda, M.; Selvaggi, G.; Stosor, V.; Lyon, G.M.; Wallace, R.M.; Gabel, J.; Stanek, D.R.; Jenkins, P.; Shiferaw, M.; Yager, P.; et al.
Abstract Background The rabies virus causes a fatal encephalitis and can be transmitted through organ transplantation. In 2013, a man developed rabies 18 months after receiving a kidney from a donor with rabies, who was not known to have been infected when the organs were procured. Three additional persons who received organs from the same donor (liver, kidney, heart), all of whom were not vaccinated for rabies before transplantation, received rabies post‐exposure prophylaxis (PEP) with rabies immune globulin and 5 doses of rabies vaccine as soon as the diagnosis of rabies was made in the donor (18 months after their transplant surgeries). We describe their clinical management. Methods As the 3 recipients were all on immunosuppressive medications, post‐vaccination serologic testing was performed using the rapid fluorescent focus inhibition test to measure rabies virus neutralizing antibodies (RVNAs). An acceptable antibody response to administration of rabies vaccine was defined as detection of RVNAs at a concentration ≥0.1 IU/mL from a serum specimen collected ≥7 days after the fifth vaccine dose. Results All 3 recipients demonstrated an acceptable antibody response despite their immunosuppressed states. More than 36 months have passed since their transplant surgeries, and all 3 recipients have no evidence of rabies. Conclusions The survival of 3 previously unvaccinated recipients of solid organs from a donor with rabies is unexpected. Although the precise factors that led to their survival remain unclear, our data suggest that PEP can possibly enhance transplant safety in settings in which donors are retrospectively diagnosed with rabies.